Mengurangi Ketakutan Terhadap Perawatan Gigi:Pendekatan Psikologis Dan Edukasi Masyarakat Kecamatan Panakkukang Kota Makassar - Amirah Maritsa; Zahrawi Astrie Ahkam; Hasrini Hasrini; Dwi Rezky Aulyah; Dewi Sartika (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Fear of dental care is a common problem that can hinder people's access to optimal dental health services. In Panakkukang District, Makassar City, this phenomenon often causes delays or avoidance of dental care, which ultimately has the potential to worsen the community's dental and oral health conditions. This study aims to reduce fear of dental care through a comprehensive psychological approach and community education. This study aims to reduce fear of dental care through a comprehensive psychological approach and community education. The methods used in this study involve providing education to the community through dental health counseling, as well as the application of psychological techniques such as relaxation and desensitization techniques to help overcome fear. Education is delivered through socialization activities at various strategic points in Panakkukang District, while psychological techniques are applied in clinical situations and in community-based simulations. The results of the study showed that this approach significantly reduced the level of fear of dental care among the local community. Participants reported increased knowledge about the importance of dental care and decreased anxiety levels when having to undergo dental care procedures. In conclusion, the approach that combines community education with psychological interventions has proven effective in reducing fear of dental care in Panakkukang District, Makassar City. Therefore, it is recommended that similar programs be implemented in other areas to improve community access to better dental health services.